2022
DOI: 10.1108/ijebr-05-2021-0350
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the effect of family business exposure on entrepreneurial implementation intention

Abstract: PurposeScholars have typically examined family business exposure as an aggregate variable. However, it is probable that this trend oversimplifies the complexity of family exposure and its nuanced influence on entrepreneurial behaviour. Thus, to extend the theoretical boundary, this inquiry investigates distinct dimensions of family exposure in Nigeria while drawing on the theory of planned behaviour.Design/methodology/approachData were collected from five public universities in Nigeria. A sample of 1,314 respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 165 publications
0
13
0
Order By: Relevance
“…On this occasion, entrepreneurial attitude was "expressed as a full mediation to the influence of creativity on entrepreneurial intention" (Kusmintarti et al, 2017, p. 33). Furthermore, Onjewu et al (2022) demonstrated that entrepreneurial attitudes mediate the relationship between family business background and entrepreneurial implementation intention. Even now, no evidence of entrepreneurial attitude is in sight in the link between religiosity and nascent entrepreneurship.…”
Section: The Mediating Role Of Attitude Towards Entrepreneurshipmentioning
confidence: 99%
See 4 more Smart Citations
“…On this occasion, entrepreneurial attitude was "expressed as a full mediation to the influence of creativity on entrepreneurial intention" (Kusmintarti et al, 2017, p. 33). Furthermore, Onjewu et al (2022) demonstrated that entrepreneurial attitudes mediate the relationship between family business background and entrepreneurial implementation intention. Even now, no evidence of entrepreneurial attitude is in sight in the link between religiosity and nascent entrepreneurship.…”
Section: The Mediating Role Of Attitude Towards Entrepreneurshipmentioning
confidence: 99%
“…Entrepreneurial self-efficacy measures one's self-competence as it concerns venture creation (Zhang et al, 2014;Onjewu et al, 2022). Ajzen (2002) described it to be the ease or difficulty of performing a behaviour conditioned by past experience and expected barriers.…”
Section: The Mediating Role Of Entrepreneurial Self-efficacymentioning
confidence: 99%
See 3 more Smart Citations